THE ROLE OF TOGURA NUADA AS A MEDIATOR IN KAILI TRIBE'S HOUSEHOLD CONFLICT RESOLUTION - Ilma, Intan Nur; Syafii, Ahmad; Mursyid, Besse Tenriabeng (LPPM STIH Putri Maharaja, 2025)
In a marriage relationship, household conflicts can be resolved in various ways, one of which is mediation by Togura Nuada, as carried out by the Kaili Tribe in Wani Lumbumpetigo Village. Alternative dispute resolution is divided into litigation (through the courts) and non-litigation (outside the courts). Mediation by Togura Nuada is a non-litigation resolution based on local wisdom, based on the concept of living law as recognized in Article 18B Paragraph (2) of the 1945 NRI Constitution. This study aims to identify the role of Togura Nuada as a mediator in household conflicts in the Kaili community, as well as supporting and inhibiting factors. This research is empirical juridical with an empirical approach. The study results show that Togura Nuada plays an active role as a mediator. Supporting factors include community culture, social legitimacy, and support systems. Inhibiting factors include limited resources and attitudes of the conflicting parties. To overcome these obstacles, adequate infrastructure, communication skills, emotional intelligence, and a deeper understanding of culture are needed.